Integrating Cognitive and Pedagogical Schema Activation Strategies in EFL Reading Comprehension - Meutia Rachmatia; Maya Setia Priyadi; Mela Suhariyanti; Izzah Azizah Al Hadi (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
Reading comprehension constitutes a fundamental cognitive skill that significantly impacts academic achievement and lifelong learning success. In contemporary educational contexts, particularly within English as a Foreign Language (EFL) settings, students frequently encounter substantial challenges in comprehending texts due to limited background knowledge, cultural disconnection, and inadequate activation of existing cognitive schematata. This comprehensive literature review synthesizes empirical research conducted between 2020 and 2025, examining the theoretical foundations, practical applications, and effectiveness of schemata activation strategies in enhancing students' reading comprehension abilities. The analysis incorporates both international perspectives and significant contributions from Indonesian researchers, providing insights into diverse educational contexts. Findings consistently demonstrate that systematic schemata activation interventions yield significant improvements in reading comprehension performance across various student populations and educational settings. This review examines multiple activation strategies, implementation frameworks, technological integrations, and factors influencing effectiveness while identifying challenges and future research directions.